Alat Deteksi Penggunaan Masker Era New Normal Covid-19 Di Sdn 1 Batu Nindan Berbasis Mikrokontroler - Atika, Putu; Putra, Putu Bagus Adidyana Anugrah (Journal of Information Technology and Computer Science, 2022)
The existence of COVID-19 has had a very negative impact on the world of education. Currently, online learning is being carried out (on the network) which requires students to use mobile phones or computers to participate in these online learning activities. However, at SDN 1 Batu Nindan, they are currently carrying out face-to-face teaching and learning activities but not as usual, namely a student turnover system so as not to create a crowd, in 1 day only half the students are absent from class capacity and change hours every 2 hours. one hour. To raise awareness of the use of masks in students and teachers pay attention to students one by one, this is a manual method. Therefore, in this profesional program research the author will discuss how to design and build a prototype for detecting the use of masks at SDN 1 Batu Nindan using the Arduino Uno microcontroller board as Teachable Machine software in input data processing and hardware in output data processing, as well as I2C LCD support modules. 16x2 and there are also LEDs and Buzzers, which are used to detect the use of masks. If the tool detects an object using a mask, the output produced by the green LED will light up and the LCD will display text and if an object is detected without a mask, the red LED will light up and the buzzer will sound and will display text on the LCD. The test results show that the tool is sensitive to light, the level of accuracy will be high if the tool is placed in sufficient light and the tool can read the presence of objects within a maximum distance of 150cm and this tool is also sensitive to the color of the mask used.